Development and preliminary validation of the Opioid Abuse Risk Screener. Issue 1 (12th May 2016) - Henrie-Barrus, Patricia; Averill, Lynnette A; Sudweeks, Richard R; Averill, Christopher L; Mota, Natalie
Prescription opioid drug abuse has reached epidemic proportions. Individuals with chronic pain represent a large population at considerable risk of abusing opioids. The Opioid Abuse Risk Screener was developed as a comprehensive self-administered measure of potential risk that includes a wide range of critical elements noted in the literature to be relevant to opioid risk. The creation, refinement, and preliminary modeling of the item pool, establishment of preliminary concurrent validity, and the determination of the factor structure are presented. The initial development and validation of the Opioid Abuse Risk Screener shows promise for effective risk stratification.